A comparative study of the microorganisms found in the vaginal flora of pill and non pill user by Pap smear. - Bayate, Aimee Sarena (1994.)
This study was conducted to identify and classify the organisms that are present in pill user and non pill users. It will determine if taking of pills cause changes in the microflora of pill (combined) user and will describe the profile of both pill and non pill user., The study use 200 prepared smears of the vagina divided equally to both pill and non pill users. The slides were collected at Dr. Ricardo Y Ladrido Memorial Hospital, Lambunao by the family planning physician with the help of the medical technologist. The profile of the patients were also gathered to provide more information about the subjects. The organisms were identified according to their basic morpholigal characteristic. The results indicate that bacilli which is the normal inhabitant of the vagina is present in 200 samples. Cocci is present in both groups but occurs more in women who are pill users. In the parasite group, Trichomonas vaginalis is present in women who are pill user and Candida is present in both groups but occur more in women who are pill users. The test for the estimation of the difference between two proportions reveal that the z values obtained from the experiment falls between the critical region which has a value of 2.58. Such value indicate that the prevalence of parasites and bacteria are equal among pill and non pill user.
Thesis (Undergraduate, Bachelor of Science in Biology) College of Arts and Sciences, University of the Philippines in the Visayas, Iloilo.
Keywords: Vaginal flora -- Microorganisms; Pap smear